The right to water as a fundamental right - Anjos, Maria do Rosário (2018)
Water is a Human Right of first necessity. We verified that water resources have been used at a rate higher than their replacement capacity, causing problems of water scarcity. This study aims to draw attention of the world community to the need to implement measures to a real social responsibility and cooperative. A review of the literature and an analysis of the various international legal instruments on water resources will be carried out to highlight the absence of social and cooperative responsibility and the need to create sanctions. It is observed that states and international organisations have failed to develop measures to curb their misuse and to overcome the shortage of water in some regions. We believe that the current situation can only be improved through the implementation of policies in terms of social responsibility and cooperative and the companies or the organisations in general.